2007
DOI: 10.1007/s10278-007-9025-8
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying the Exploration of Volumetric Images: Development of a 3D User Interface for the Radiologist’s Workplace

Abstract: Volumetric imaging (computed tomography and magnetic resonance imaging) provides increased diagnostic detail but is associated with the problem of navigation through large amounts of data. In an attempt to overcome this problem, a novel 3D navigation tool has been designed and developed that is based on an alternative input device. A 3D mouse allows for simultaneous definition of position and orientation of orthogonal or oblique multiplanar reformatted images or slabs, which are presented within a virtual 3D s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The VRG is built upon 'virtusMED' (virtual scenes for medical education and diagnostics), a system that allows for a new kind of interactive visualization of volumetric medical images [18,19] usable for education or diagnosis [20]. Based on CT and MRI data sets in DICOM [21] format as well as on data from the Visible Human Project [22] virtusMED creates a virtual patient that can be explored in real-time by an ultrasound-like probe, a head-mounted display and/or a freely movable flat panel.…”
Section: The Virtx Systemmentioning
confidence: 99%
“…The VRG is built upon 'virtusMED' (virtual scenes for medical education and diagnostics), a system that allows for a new kind of interactive visualization of volumetric medical images [18,19] usable for education or diagnosis [20]. Based on CT and MRI data sets in DICOM [21] format as well as on data from the Visible Human Project [22] virtusMED creates a virtual patient that can be explored in real-time by an ultrasound-like probe, a head-mounted display and/or a freely movable flat panel.…”
Section: The Virtx Systemmentioning
confidence: 99%
“…In an earlier work 14 , we showed that radiologists and laypersons had similar interaction performance when expert knowledge was not required, so we hypothesized that we could use naïve laypersons to evaluate different image navigation techniques, with results that would generalize to radiologists performing clinical tasks. For example, we had observed a lot of forward and backward scrolling during a radiology look-alike task with naïve students as subjects 9 and backward and forward scrolling in stack mode by radiologists has been similarly noted by others [11][12][13] . As a final, tertiary, issue, we were interested whether a group of naïve students would have similar performance and preferences to radiologists for the three techniques.…”
mentioning
confidence: 64%
“…Although many of the storage and display hurdles of digital radiology have been met, many humancomputer interaction problems remain [7][8][9] . Some recent work has addressed these problems by making the presentation of the data more nearly 3D.…”
mentioning
confidence: 99%
“…Instead, the image can be repositioned or reoriented by pressing a certain button on the controller, comparable to the user interaction of moving a window on a computer's desktop. For this approach, ideas are being adopted from previous work that made use of a customized 2D-3D mouse (37).…”
Section: Resultsmentioning
confidence: 99%